Pigs in the Pantry: Fun with Math and Cooking - Axelrod, Amy.; McGinley-Nally, Sharon (New York, N.Y. : Simon & Schuster Books for Young Readers, 1997)
Mr. Pig and the piglets try to cook Mrs. Pig's favorite dish to cheer her up when she's sick. Includes a recipe for chili.
"Ages 4-9"--P. 4 of cover.
Keywords: Cookery -- Fiction; Pigs -- Fiction